2019
DOI: 10.1002/mgg3.857
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of genes associated with head and neck squamous cell carcinoma by integrated bioinformatics methods

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers worldwide, exhibiting high morbidity and mortality. The prognosis of HNSCC patients has remained poor, though considerable efforts have been made to improve the treatment of this cancer. Therefore, identifying significant differentially expressed genes (DEGs) involved in HNSCC progression and exploiting them as novel biomarkers or potential therapeutic targets for HNSCC is highly valuable. Methods Overlapping differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…The construction of the gene prediction model has been applied in many tumors, such as esophageal cancer, lung cancer, and thyroid cancer, but there are only few relevant studies on head and neck tumors. In some studies, by comparing three separate comprehensive gene expression omnibus (GEO) databases, researchers claimed that overlapping differentially expressed genes [ 29 ] like SPP1, POSTN, and COL1A2 could be used as potential diagnostic indicators of head and neck carcinoma. However, classical factors of head and neck tumors were not taken into account in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the gene prediction model has been applied in many tumors, such as esophageal cancer, lung cancer, and thyroid cancer, but there are only few relevant studies on head and neck tumors. In some studies, by comparing three separate comprehensive gene expression omnibus (GEO) databases, researchers claimed that overlapping differentially expressed genes [ 29 ] like SPP1, POSTN, and COL1A2 could be used as potential diagnostic indicators of head and neck carcinoma. However, classical factors of head and neck tumors were not taken into account in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the members of MMPs family have been investigated as tumor markers, so we further explored the clinical significance of serum MMP3 in NPC. Several studies have reported that the higher MMP3 expression in the stromal compartment compared to normal tissues [10,11,13]. MMP3 is expressed primarily by stromal cells, including fibroblast cell and tumor-infiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the higher MMP3 expression in the stromal compartment compared to normal tissues 10 , 11 , 13 . MMP3 is expressed primarily by stromal cells, including fibroblast cell and tumor-infiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For data validation, the gene expression profiles of 139 COAD samples from GSE21510 and GSE110224, 1098 LUAD samples from GSE30219, GSE31210, GES3141, GSE37745, GSE50081, and GSE68465, 211 LUSC samples from GSE43580, GSE73403, and GSE67061 and 80 HNSC samples from GSE6631 and GSE13601 were obtained from the GEO data portal 8 and analyzed using R language (Wang et al, 2017;Jin and Yang, 2019;Miao et al, 2019;Yang H. et al, 2019;Gao et al, 2020;Li et al, 2020;Qu et al, 2020). Patients in four cancers were divided into upregulated groups and downregulated groups base on the median expression of SPP1 (Zhao et al, 2018).…”
Section: Correlated Genes In Geomentioning
confidence: 99%